Biochemical Importance and Kinetic Studies of Placental Alkaline Phosphatase Isoenzyme as a Predictor Marker of Primary Malignancies - Noor Kareem Aead; Fadhil Jawad Al-Tuma; Rana Majeed Hameed3; Riyadh Abd-Alrasool Hne (Indian Journal of Forensic Medicine & Toxicology, 2021)
ung cancer is the main cause of cancer-related death worldwide and conventional diagnostic strategies must be improved. developments of a simple method or techniques which would enable researchers to identify and validate the early screening biomarker of lung cancer patients. The aims of this article were to review the background documents on the state of the art of the scientific literature in studies that used Placental alkaline phosphatase in the diagnostic of lung cancer also to suggest areas where further research is needed, either to deal with gaps in the knowledge related to employ the heat stability of Placental alkaline phosphatase or assessment the quantitation methods of the isoenzyme.